Speckle tracking echocardiography strain analysis for the assessment and monitoring of myocardial mechanics after pediatric cardiac surgery. (4th February 2022) - Cantinotti, M; Marchese, P; Franchi, E; Assanta, N; Van Den Eynde, J; Shelby, K
Abstract: Funding Acknowledgements: Type of funding sources: None. Background. Speckle-tracking echocardiography (STE) is a relatively new ultrasound technique that exploits acoustic reflections and artifacts within the ultrasonic window, with the aim of analyzing global myocardial deformation and segmenting. STE has proved to be more sensitive in identifying a myocardial dysfunction so gained increasing value in the evaluation of congenital heart diseases (CHD) even though its use, in pediatric cardiac surgery, is still limited. The present study aims to evaluate the global and left ventricular (LV) systolic impairment after pediatric cardiac surgery by STE strain (ε) analysis.  Methods: We prospectively enrolled 120 children undergoing cardiac surgery for CHD. Echocardiography was performed at four different times: pre-operatively, 12-36 hours (Time-1), 3-5 days (Time-2), 6-8 days (Time-3). Images were obtained in the 4-2-and 3 apical chamber's views to derive LV global and regional (basal/mid/apical) ε values. Results. We collected data from 332 examinations in 120 children (mean age: 2.33 ±3.91, range: 0-16 years) at different post-operative times. 120 age-matched healthy children (3.1 ± 4.2 years) served as controls. All global, basal, and mid LVε values reduced after surgery; the lowest values were at Time-1 (p < 0.0001) but increased thereafter. At discharge, all global, basal, and mid LVε values persisted lower than pre-operatively and healthy children (p < 0.05). Instead, apical segments (lowest at baseline), increased after surgery (p < 0.0001), but remained lower compared to controls. LV ejection fraction (LVEF) decreased at Time-1 (p = 0.0003) but promptly recovered to Time-2, to standardize at Time-3. Conclusions. Despite LVEF was normalized by the discharge, STE ε has shown a systolic impairment after cardiac surgery that disclosed a gradual improvement but still uncomplete normalization at discharge. Regional STE differences revealed a discrepancy base-apex: apical segments, contrary to all the other regions, showed hypercontractility after surgery. The slower recovery of LVε values compared to LVEF, suggests that STE ε analysis may be more accurate in the follow-up of mild LV post-surgical impairment.